130k views
4 votes
F(x) = x2. What is g(x)?
g(x).
5
-(1.4)
f(x)
-5
5
-5

User Xypron
by
5.4k points

1 Answer

4 votes

Answer:

Explanation:

– P2(0) = f(0) ⇒ c = f(0).

– P

0

2

(0) = f

0

(0), P0

2

(x) = 2ax + b ⇒ b = f

0

(0).

– P

00

2

(0) = f

00(0), P00

2

(x) = 2a ⇒ a =

f

00(0)

2

.

• So, we should take P2(x) = f

00(0)

2

x

2 + f

0

(0)x + f(0).

User Lightyrs
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.